Disasters and Recoveries - Gourio, François (American Economic Review, 2008)
Twenty years ago, Thomas A. Rietz (1988) showed that infrequent, large drops in consumption make the theoretical equity premium large. Recent research has resurrected this ‘disaster’explanation of the equity premium puzzle. Robert J. Barro (2006) measures disasters during the XXth century, and …nds that they are frequent and large enough, and stock returns low enough relative